The Auschwitz volunteer : beyond bravery - Pilecki, Witold, 1901-1948; Garlinski, Jarek; Polish Underground Movement (1939-1945) Study Trust (2012)
September 1940. Polish Army officer Witold Pilecki deliberately walked into a Nazi German street round-up in Warsaw and became Auschwitz Prisoner No. 4859. He had volunteered for a secret undercover mission: smuggle out intelligence about the new German concentration camp, and build a resistance organization among prisoners. Pilecki's clandestine intelligence, received by the Allies in 1941, was among earliest. He escaped in 1943 after accomplishing his mission. Dramatic eyewitness report, written in 1945 for Pilecki's Polish Army superiors, published in English for first time. --amazon.com.
Captain Pilecki's covering letter to Major general Tadeusz Petcynski -- Captain Witold Pilecki's 1945 Auschwitz report.
"This translation is based on the original typescript of Captain Witold Pilecki's 1945 Report held at the Polish Underground Movement Study Trust in London."--Page xix.
Includes bibliographical references and index.
Keywords: Pilecki, Witold, -- 1901-1948.; Pilecki, Witold, -- 1901-1948.; Pilecki, Witold, -- 1901-1948.; World War, 1939-1945 -- Underground movements -- Poland; Armed Forces -- Officers; Underground movements, War; Poland -- Armed Forces -- Officers -- Biography; Poland; Biography; Auschwitz (Concentration camp); Auschwitz (Concentration camp); Auschwitz (Concentration camp)